Diversification–specialisation dynamics in Madagascar’s clove landscapes: the role of rice land availability - Manon Desmurs; Julien Sarron; Elisa Rahantarivelo; Pascal Danthu; Éric Malézieux; Isabelle Michel (Agroforestry Systems, 2026)
Understanding why agroforestry systems are more or less diversified in species is essential for sustaining livelihoods and ecological functions in perennial-crop landscapes. In eastern Madagascar, clove-based agroforestry dominates upland production systems, yet field structure varies markedly across short distances. We clarified the association between landscape-scale rice production capacity and agroforestry diversification–specialisation dynamics in clove-dominated landscapes. We combined tree-inventory data from 54 plots with a quantitative proxy of village-level rice self-sufficiency across three neighbouring villages with contrasting access to irrigated lowlands. Four agroforestry system types, namely complex agroforests, diversified cash-oriented systems, clove-dominated systems and simple parklands, were identified through rule-based classification. Village-level access to irrigated lowlands was strongly associated with their distribution. In rice-surplus villages (Ampahibe, + 15% sufficiency), 94% of plots were complex agroforests integrating fruit and forest species (35% and 45% of stems, respectively) with mean species richness of 6.4 ± 3.0 species per plot. In rice-deficit uplands (Andampy, − 90% sufficiency), 50% of plots were clove-dominated systems where clove accounted for 70% of stems and species richness declined to 3.6 ± 2.1 species per plot. Contrary to expectations, within-village topography did not influence perennial species composition. Village-scale differentiation aligned with food-security constraints operating at household level rather than ecological sorting. Contemporary agroforestry configurations result from interactions between historical trajectories (colonial coffee plantations, farmer-led clove expansion, farmer-driven diversification since independence) and present-day rice availability, which filters diversification or specialisation trajectories. Maintaining agroforestry diversity in clove-producing regions depends as much on securing stable rice production systems as on managing perennial-crop markets.

From shifting rice cultivation (tavy) to agroforestry systems: a century of changing land use on the East Coast of Madagascar - Juliette Mariel; Eric Penot; Vanesse Labeyrie; Hasina Herimandimby; Pascal Danthu (Agroforestry Systems, 2023)

Coming from elsewhere: the preponderance of introduced plant species in agroforestry systems on the east coast of Madagascar - Pascal Danthu; Isabelle Michel; Stéphanie M. Carrière; Vanesse Labeyrie; Bakolimalala Rakouth; Julien Sarron; Juliette Mariel; Dominique Lasserre; Eric Penot (Agroforestry Systems, 2022)

Not all species will migrate poleward as the climate warms: The case of the seven baobab species in Madagascar - Mario M. Tagliari; Pascal Danthu; Jean‐Michel Leong Pock Tsy; Cyrille Cornu; Jonathan Lenoir; Vítor Carvalho‐Rocha; Ghislain Vieilledent (Global Change Biology, 2021)
It is commonly accepted that species should move toward higher elevations and latitudes to track shifting isotherms as climate warms. However, temperature might not be the only limiting factor determining species distribution. Species might move to opposite directions to track changes in other climatic variables. Here, we used an extensive occurrence data set and an ensemble modelling approach to model the climatic niche and to predict the distribution of the seven baobab species (genus Adansonia ) present in Madagascar. Using climatic projections from three global circulation models, we predicted species’ future distribution and extinction risk for 2055 and 2085 under two representative concentration pathways (RCPs) and two dispersal scenarios. We disentangled the role of each climatic variable in explaining species range shift looking at relative variable importance and future climatic anomalies. Four baobab species ( Adansonia rubrostipa , Adansonia madagascariensis , Adansonia perrieri¸ and Adansonia suarezensis ) could experience a severe range contraction in the future (>70% for year 2085 under RCP 8.5, assuming a zero‐dispersal hypothesis). For three out of the four threatened species, range contraction was mainly explained by an increase in temperature seasonality, especially in the North of Madagascar, where they are currently distributed. In tropical regions, where species are commonly adapted to low seasonality, we found that temperature seasonality will generally increase. It is, thus, very likely that many species in the tropics will be forced to move equatorward to avoid an increase in temperature seasonality. Yet, several ecological (e.g., equatorial limit, or unsuitable deforested habitat) or geographical barriers (absence of lands) could prevent species to move equatorward, thus increasing the extinction risk of many tropical species, like endemic baobab species in Madagascar.

The baobabs of the Comoro Islands: some biogeographical factors towards the protection and conservation of a neglected asset - Maoulida Mohamed Abdillahi; Cyrille Cornu; Raïma Fadul; Michel Charpentier; Edmond Roger; Bakolimalala Rakouth; Jean-Michel Leong Pock Tsy; Pascal Danthu (Tropical Ecology, 2019)

Clove based cropping systems on the east coast of Madagascar: how history leaves its mark on the landscape - Natacha Arimalala; Eric Penot; Thierry Michels; Vonjison Rakotoarimanana; Isabelle Michel; Harisoa Ravaomanalina; Edmond Roger; Michel Jahiel; Jean-Michel Leong Pock Tsy; Pascal Danthu (Agroforestry Systems, 2019)

Taking into account local practices and indigenous knowledge in an emergency conservation context in Madagascar - Chloé N. Marie; Nicole Sibelet; Michel Dulcire; Minah Rafalimaro; Pascal Danthu; Stéphanie M. Carrière (Biodiversity and Conservation, 2009)

Chloroplast DNA phylogeography suggests a West African centre of origin for the baobab, Adansonia digitata L. (Bombacoideae, Malvaceae) - JEAN‐MICHEL LEONG POCK TSY; ROSELYNE LUMARET; DIANA MAYNE; ABDALLAHI OULD MOHAMED VALL; YAHIA I. M. ABUTABA; MAURICE SAGNA; SOAHARIN’NY ONY RAKOTONDRALAMBO RAOSETA; PASCAL DANTHU (Molecular Ecology, 2009)
The African baobab ( Adansonia digitata L.) is an emblematic, culturally important, and physically huge tropical tree species whose natural geographical distribution comprises most of tropical Africa, but also small patches of southern Arabia, and several Atlantic and Indian Ocean islands surrounding the African continent, notably including Madagascar. We analysed the polymerase chain reaction–restriction fragment length polymorphism of five chloroplast DNA fragments obtained from 344 individuals of A. digitata collected from 74 populations covering the entire extant distribution range of the species. Our goal was to reconstruct the phylogeographical history of the species and, if possible, to identify its centre of origin, which has been a subject of controversy for many decades. We identified five haplotypes whose distribution is clearly geographically structured. Using several species of Adansonia and of closely related genera as outgroups, the haplotypes showed a clear phylogeographical pattern of three groups. Two are phylogenetically related to the outgroup taxa, and are distributed in West Africa. The third group is substantially more differentiated genetically from outgroup species, and it corresponds to southern and eastern Africa, Arabia and the Indian Ocean islands, including Madagascar. According to our results, the tetraploid A. digitata , or its diploid progenitor, probably originated in West Africa and migrated subsequently throughout the tropical parts of that continent, and beyond, by natural and human‐mediated terrestrial and overseas dispersal.

Essential oil production increases value of Psiadia altissima fallows in Madagascar’s eastern forests - Pascal Danthu; Miarantsoa Rakotobe; Pascale Mauclère; Hanitra Andrianoelisoa; Olivier Behra; Voninavoko Rahajanirina; Barbara Mathevon; Eliane Ralembofetra; Philippe Collas de Chatelperron (Agroforestry Systems, 2008)

Genetic Diversity of Dalbergia monticola (Fabaceae) an Endangered Tree Species in the Fragmented Oriental Forest of Madagascar - Olivarimbola Andrianoelina; Hery Rakotondraoelina; Lolona Ramamonjisoa; Jean Maley; Pascal Danthu; Jean-Marc Bouvet (Biodiversity and Conservation, 2006)